Loneliness and Substance Use: Investigating Emotion Dysregulation as a Mediator - Muñoz, Nayelli; Santoso, Agus (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the mediating role of emotion dysregulation in the relationship between loneliness and substance use among Indonesian adults. Methods and Materials: A descriptive correlational design was employed with a sample of 430 participants, selected based on the Morgan and Krejcie table. Participants completed standardized self-report questionnaires: the UCLA Loneliness Scale (Version 3), the Difficulties in Emotion Regulation Scale (DERS), and the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST). Data were analyzed using SPSS-27 and AMOS-21. Pearson correlation analysis examined the bivariate relationships among variables, and Structural Equation Modeling (SEM) was used to test the hypothesized mediating model, including assessments of model fit using chi-square, RMSEA, CFI, TLI, and other indices. Findings: Pearson correlation analysis showed that loneliness was significantly and positively correlated with emotion dysregulation (r = .49, p < .001) and substance use (r = .38, p < .001), while emotion dysregulation was strongly associated with substance use (r = .53, p < .001). The SEM results confirmed a good model fit (χ² = 121.38, df = 48, RMSEA = 0.061, CFI = 0.96, TLI = 0.94), and indicated that emotion dysregulation significantly mediated the relationship between loneliness and substance use. The indirect effect (β = 0.26, p < .001) was substantial, and the total effect of loneliness on substance use (β = 0.50, p < .001) exceeded the direct effect (β = 0.24, p < .001), confirming partial mediation. Conclusion: The findings suggest that emotion dysregulation is a significant psychological mechanism through which loneliness contributes to substance use. Targeting emotion regulation strategies may be effective in mitigating substance-related risks in emotionally vulnerable individuals, particularly those experiencing chronic loneliness.